A prova como direito humano e direito fundamental das partes do processo judicial - Cleber Lucio de Almeida (2011)
The objective of this thesis is to analyze the role of evidence from the perspective of International Human Rights Law, and the Brazilian Federal Constitution of 1988. We seek to verify whether evidence is a right of the parties in civil and labor cases, and whether the status of a human and fundamental right can be attributed to this right, if it is confirmed to exist.Based on a critical analysis of the rules that make up International Human Rights Law, the Brazilian Federal Constitution of 1988 and legislation and legal doctrine, we reached the conclusion that the parties in judicial proceedings have human and fundamental proceduralrights, which together make up what has been called the minimum procedural existence; that evidence is a human, fundamental right of the parties in judicial proceedings; and that the Rule of Law requires the participation of the parties in the definition of their rights andobligations, conferring upon them the condition of subjects of the proceeding, and not just subjects to the proceeding, and is consolidated by this participation. The human and fundamental nature of the right to evidence grants it the condition of a right inherent to humandignity and to the dignity of this instrument of this same dignity, and attributes its own legal regime to human and fundamental rights, which have a supra-legal nature, and to constitutionally prohibited suppression, as well as allowing accusations of its violation to the Inter-American Commission on Human rights.